2007
DOI: 10.1037/0033-295x.114.3.539
|View full text |Cite
|
Sign up to set email alerts
|

A temporal ratio model of memory.

Abstract: A model of memory retrieval is described. The model embodies 4 main claims: (a) temporal memory--traces of items are represented in memory partly in terms of their temporal distance from the present; (b) scale-similarity--similar mechanisms govern retrieval from memory over many different timescales; (c) local distinctiveness--performance on a range of memory tasks is determined by interference from near psychological neighbors; and (d) interference-based forgetting--all memory loss is due to interference and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

71
1,197
9
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 723 publications
(1,306 citation statements)
references
References 264 publications
(532 reference statements)
71
1,197
9
4
Order By: Relevance
“…The overlap between our current study and the previous LTM study using analogous tasks and materials lends weight to the notion of scale‐invariance in memory mechanisms [Brown et al, 2007], as have been previously demonstrated in free recall tasks, where the rate of item recall was unvarying across recall span (day, week, year) and even across from the past to the prospective future [Maylor et al, 2001]. Those previous behavioral findings imply that scale‐invariance is a form of self‐similarity in that the holistic pattern can exist at multiple levels of magnification [and even across different memory systems, e.g., Maylor, 2002].…”
Section: Discussionsupporting
confidence: 51%
“…The overlap between our current study and the previous LTM study using analogous tasks and materials lends weight to the notion of scale‐invariance in memory mechanisms [Brown et al, 2007], as have been previously demonstrated in free recall tasks, where the rate of item recall was unvarying across recall span (day, week, year) and even across from the past to the prospective future [Maylor et al, 2001]. Those previous behavioral findings imply that scale‐invariance is a form of self‐similarity in that the holistic pattern can exist at multiple levels of magnification [and even across different memory systems, e.g., Maylor, 2002].…”
Section: Discussionsupporting
confidence: 51%
“…Note that the value of c was the same for all list lengths; that is, all 90 data points are being accounted for by a single free parameter. 2 SIMPLE produces the appropriate position error gradients for operation span using the same core ideas implemented to account for recall in standard serial recall tasks and tasks thought to tap other memory systems including sensory, short-term, working, and long-term memory (see Brown et al, 2007;. The distractor activity in the operation span task serves the same function as in the continual distractor task: it spaces the to-be-remembered items out in time, and it is the distinctiveness of each item, relative to its near neighbors, at the time of test that determines recall probability.…”
Section: Results and Modelingmentioning
confidence: 99%
“…Unfortunately, the nature of the context is controversial. Alternative suggestions include time, temporal position within a list, list position, and position from the ends of the list (see Botvinick & Plaut, 2006;Brown, Neath, & Chater, 2007;Brown, Preece, & Hulme, 2000;Burgess & Hitch, 1999;Farrell & Lewandowsky, 2002Grossberg & Pearson, 2008;Henson, Norris, Page, & Baddeley, 1996;Lewandowsky & Farrell, 2008).…”
Section: Abstract: Hologram Memory Learning Recallmentioning
confidence: 99%